The Silent Struggle: How Social Anxiety Impacts English Language Proficiency in University Students - Lahamu, Moh Adriansyah; Syawal, Deys Triawati; Ibrahim, Erta Putri; Mertosono, Sri (Lembaga Publikasi Ilmiah Dwipantara, 2025)
In the era of globalization and digital transformation, mastering foreign languages, especially English, has become an essential skill in various aspects of life. This ability not only plays a role in cross-cultural communication, but also determines individual success in education, work, and global social interactions. English is now not just a subject, but a key tool in accessing information, building international relations, and participating in the global economy. However, behind the importance of mastering English, significant psychological challenges arise, namely social anxiety. Social anxiety is defined as excessive fear or nervousness in social situations, especially when speaking in front of other people. In the context of foreign language learning, social anxiety can manifest in the form of fear of making mistakes, fear of being evaluated, and worry about negative judgments from others. Recent studies show that individuals who have high levels of social anxiety tend to experience difficulties in speaking skills, even when they have a good command of grammar or vocabulary. This study aims to explore the relationship between social anxiety and English language skills among college students, specifically focusing on the correlation between anxiety and self-confidence in speaking a foreign language. Utilizing a quantitative survey design with 6 respondents from Gorontalo State University, the research collected data via online questionnaires and analyzed it using descriptive and Pearson correlation analysis. The main findings indicate a significant negative correlation (r = -0.56) between anxiety and self-confidence, suggesting that higher anxiety levels are associated with lower self-confidence in speaking English. This highlights the importance of addressing psychological factors, such as social anxiety, in English language education at the university level to foster more effective and holistic language learning strategies